Respon Pertumbuhan dan Hasil Tanaman Padi Merah (Oryza Nivara L.) Varietas Inpari 24 Gabusan terhadap Macam Pupuk Npk dan Konsentrasi Pupuk Nanosilika - Ramdan, Muhammad; Maryani, Yekti; Pamungkas, Djoko Heru (JURNAL ILMIAH AGROUST, 2022)
The purpose of this study was to determine the type of NPK fertilizer and the concentration of nanosilica fertilizer that provided good growth and yield for the local red rice variety Inpari-24 Gabusan. This research was conducted from January to May 2022, taking place at the PAS “Lestari Makmur” Self-Help Agriculture and Rural Training Center, Jalan Wates Km. 12 Semampir Hamlet, Argorejo Village, Sedayu District, Bantul Regency, Yogyakarta. This study consisted of 2 factors, namely the first factor, the NPK Phonska, Mutiara, Yaramila fertilizers and the second factor, namely the concentration of 1%, 1.5%, and 2% Nanosilika fertilizer. This study was conducted with 3 repetitions of each factor and arranged in a Complete Randomized Block Design RAKL. The observed variables included plant height, number of tillers per hill, fresh chestnut weight, dry shoot weight, number of productive tillers per hill, panicle length, percentage of filled grain, 1000 grain weight, and grain weight per hectare. Data analysis was carried out on the results of observations using variance at a 5% level, the differences between treatments were tested with DMRT Duncan's multiple range test at a level of 5%. Treatment of various NPK fertilizers and nanosilica fertilizer concentrations on the growth and yield of red rice of the Inpari-24 gabusan variety showed no interaction with all observed variables. Treatment of various NPK fertilizers on the growth and yield of the red rice variety Inpari-24 Gabusan showed no significant difference in growth and yield. Treatment of nanosilica fertilizer concentrations on the growth and yield of the red rice variety Inpari-24 gabusan showed no significant difference in growth and yield, except for plant height, number of tillers, and percentage of filled grain.